Umar bin ’Abdul ’Aziz’s Ijtihad on Zakat Management - Nazhif Dhiya’elhaq, Muhammad Ghossan; Labib, Muhammad Alfreda Daib Insan (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2023)
This research is based on the issue of ineffective zakat management. In response to this situation, a study was conducted on the concept of zakat management according to Umar bin Abdul Aziz. The purpose of this research is to provide alternative solutions to the current problems in zakat management. The research adopts a library research or literature-based method with a descriptive-analytical approach, drawing from books, journals, and other scholarly works that serve as the object of study. The primary source used in this research is the book "al-Khalifah al-Rasyid wa al-Muslih al-Kabir ‘Umar ibn ‘Abdul ‘Aziz" by Prof. Dr. ‘Ali Muhammad al-Shalabi, which contains the biography of Umar bin Abdul Aziz and his zakat management policies. The research concludes that there are five strategies in Umar bin Abdul Aziz’s concept of zakat management and distribution, including: 1) being based on the Qur’an and the Sunnah of the Prophet, 2) accelerating the distribution of zakat to the rightful recipients (ashnaf), 3) reforming the quality of human resources for zakat officials, 4) distributing zakat based on regional zakat income, and 5) Umar bin Abdul Aziz’s ijtihad (independent reasoning) in some objects subject to mandatory zakat. The impacts of this concept include: 1) surplus zakat income, 2) recipients of zakat becoming contributors (muzaki), and 3) achieving economic stability and community welfare.